Preclinical testing of Peruvian anti-bothropic anti-venom against Bothrops andianus snake venom - Schneider, Francisco S. (2012)
Bothrops andianus is a venomous snake found in the area of Machu Picchu (Peru). Its venom is not included in the antigenic pool used for production of the Peruvian anti-bothropic anti-venom. B. andianus venom can elicit many biological effects such as hemorrhage, hemolysis, proteolytic activity and lethality. The Peruvian anti-bothropic anti-venom displays consistent cross-reactivity with B. andianus venom, by ELISA and Western Blotting and is also effective in neutralizing the venom's toxic activities.